2017
DOI: 10.1159/000477885
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy Promotes Cardiomyocyte Autophagy and Survival during Hypoxia

Abstract: Background: Autophagy plays an important role in cardiovascular disease. Controversy still exists regarding the effect of autophagy on ischemic/hypoxic myocardium. Cardiac shock wave therapy (CSWT) is an effective alternative treatment for refractory ischemic heart disease. Whether CSWT can regulate cardiomyocyte autophagy under hypoxic conditions is not clear. We established a myocardial hypoxia model using the H9c2 cell line and performed shock waves (SWs) treatment to evaluate the effect of SW on autophagy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Among the five previously identified ARGs associated with MM, HIF1A is the most widely studied (59,60). Hypoxia, a central characteristic for cancer incidence and progression, occurs when most types of cancer are evolving (59)(60)(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the five previously identified ARGs associated with MM, HIF1A is the most widely studied (59,60). Hypoxia, a central characteristic for cancer incidence and progression, occurs when most types of cancer are evolving (59)(60)(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five previously identified ARGs associated with MM, HIF1A is the most widely studied (59,60). Hypoxia, a central characteristic for cancer incidence and progression, occurs when most types of cancer are evolving (59)(60)(61)(62)(63)(64). HIF1A is a hypoxia-inducible factor, and constitutive expression of HIF1A in MM indicates that suppression of HIF1A-mediated transcription could become a favorable target for MM (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is activated and serves as an energy sensor to control cell cycle progression and autophagy in cells under nutrient deprivation or stressed conditions [30, 31]. AMPK not only directly phosphorylates cyclin-dependent kinase inhibitor p27 kip1 at Thr198 to stabilize p27 kip1 in the nucleus but also indirectly activates FoxO3a to induce p27 kip1 expression, which, in turn, arrests the cell cycle at G 1 phase [25, 30].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of I/R injury is complicated and unclear, and may be related to factors such as mitochondrial dysfunction, overproduction of reactive oxygen species (ROS), reduction of nitric oxide bioavailability, and intracellular calcium overload [3,4]. Recently, a study has shown that shock wave therapy may serve as an effective option for ischemic heart disease [5]. Nevertheless, no effective therapy for preventing reperfusion injury is available to date [6]; thus, further study is urgently needed.…”
Section: Introductionmentioning
confidence: 99%